2010
DOI: 10.4314/njps.v22i1-2.54865
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system depressant activity of Russelia equisetiformis

Abstract: Summary:The central nervous system depressant activity of the crude methanol extract (REC) and fractions (RE1, RE2, and RE3) of Russelia equisetiformis were evaluated in mice using the following models: amphetamine -induced stereotypy, picrotoxin -induced convulsion and phenobarbitone sleeping time. At 200-400mg/kg, REC significantly increased phenobarbitone-sleeping time (p< 0.05) in a dose-dependent manner and also reduced the sleep latency significantly (p< 0.05). The fractions, at doses 1.5mg/kg for RE1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…Carrageenan‐induced paw puffiness has been most notably used in experimental animal models for the assessment of acute inflammation and is considered to be biphasic, with the early phase (1‐2 hours) of the carrageenan model being principally mediated by histamine, serotonin, and enhanced synthesis of autacoids in injured tissue, while the late phase is mediated by bradykinin, leukotrienes, polymorphonuclear cells, and prostaglandins made by tissue macrophages . In our study, the crude methanolic acetate fraction of P .…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Carrageenan‐induced paw puffiness has been most notably used in experimental animal models for the assessment of acute inflammation and is considered to be biphasic, with the early phase (1‐2 hours) of the carrageenan model being principally mediated by histamine, serotonin, and enhanced synthesis of autacoids in injured tissue, while the late phase is mediated by bradykinin, leukotrienes, polymorphonuclear cells, and prostaglandins made by tissue macrophages . In our study, the crude methanolic acetate fraction of P .…”
Section: Discussionmentioning
confidence: 86%
“…stratoites produced significant inhibition of paw puffiness from 0 minutes to 3 hours, which was comparable with the effect of standard ibuprofen. A possible mechanism for the extract's observed anti‐inflammatory activity might be its ability to reduce the release of histamine, serotonin or kinin‐like substances or biosynthesis of prostaglandins …”
Section: Discussionmentioning
confidence: 99%
“…Gamma-aminobutyric acid (GABA) is evidenced to be the major inhibitory neurotransmitter of CNS and several anxiolytic, muscle relaxant and sedative-hypnotic drugs exhibit their action via GABA [36]. Thus it can be pretended that the methanolic seed extract may act by commencing the GABAergic inhibition of the CNS through membrane hyperpolarization that lead to a reduction in the firing rate of critical neurons in the brain or the extract may simply activate the GABA receptors directly [37]. Again, research has shown that plants containing alkaloids, flavonoids and tannins are useful for the treatment of many CNS disorders as they reduce the locomotor activity of the CNS [38] which led to the postulation that these compounds may act as benzodiazepine like molecules [39].…”
Section: Discussionmentioning
confidence: 99%
“…Different anxiolytic, muscle relaxant, sedative-hypnotic drugs are elucidation their action through GABA A , therefore it is possible that extract of P. longum may acts by potentiating GABAergic inhibition in the CNS via membrane hyperpolarization which leads to a decrease in the firing rate of critical neurons in the brain or may be due to direct activation of GABA receptor by the extract 15 . The fruits of Piper longum L. contains amide alkaloids, flavonoids, essential oils, lignans and the root contains amide alkaloids but the phytochemical compositions of the leaves is still unknown.…”
Section: Discussionmentioning
confidence: 99%